2023
DOI: 10.3390/su15075640
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Flexural Behavior of Mortar Beams Strengthened with Recycled Plastic Mesh

Abstract: The generation of plastic waste is increasing all over the world at an alarming rate, therefore raising concerns related to its disposal. As space for landfilling is becoming scarce and as incinerating the plastic waste leads to the release of toxic elements into the environment, recycling becomes a viable and an attractive option in pursuit of sustainable development. This paper investigates the flexural behavior of mortar beams reinforced with recycled plastic mesh. To achieve this objective, 27 mortar beams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…On average, the initial cracking energy consumption of TRLC thin plates doped with HPMC decreased by 67%, while the flexural toughness index showed consistent increases, with some reaching up to 11.40 times higher values. (5) In this study, we focused solely on particular textile types and HPMC doping ratios, analyzing only the bending behavior of the specimens. Future research could explore the impact of various textile varieties and diverse doping ratios of HPMC on TRLC.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the initial cracking energy consumption of TRLC thin plates doped with HPMC decreased by 67%, while the flexural toughness index showed consistent increases, with some reaching up to 11.40 times higher values. (5) In this study, we focused solely on particular textile types and HPMC doping ratios, analyzing only the bending behavior of the specimens. Future research could explore the impact of various textile varieties and diverse doping ratios of HPMC on TRLC.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Gardiner et al [2] proved it is an effective reinforcement method by incorporating a fabric net with fixed intervals in the warp and weft yarns in cementitious materials. It also has been shown that the mechanical properties of concrete can be improved by incorporating textiles into the concrete [3][4][5]. The bonding strength between the textile and the concrete matrix influences the synergetic performance of the TRC [6].…”
Section: Introductionmentioning
confidence: 99%